Microchemical analysis of Leonardo da Vinci’s lead white paints reveals knowledge and control over pigment scattering properties - Gonzalez, Victor; Hageraats, Selwin; Wallez, Gilles; Eveno, Myriam; Ravaud, Elisabeth; Réfrégiers, Matthieu; Thoury, Mathieu; Menu, Michel; Gourier, Didier (Scientific reports, 2020)
Leonardo da Vinci (1452–1519) is a key artistic and scientific figure of the Renaissance. He is renowned for his science of art, taking advantage of his acute observations of nature to achieve striking pictorial results. This study describes the analysis of an exceptional sample from one of Leonardo’s final masterpieces: The Virgin and Child with St. Anne (Musée du Louvre, Paris, France). The sample was analyzed at the microscale by synchrotron-based hyperspectral photoluminescence imaging and high-angular X-ray diffraction. The results demonstrate Leonardo’s use of two subtypes of lead white pigment, thus revealing how he must have possessed a precise knowledge of his materials; carefully selecting them according to the aesthetical results he aimed at achieving in each painting. This work provides insights on how Leonardo obtained these grades of pigment and proposes new clues regarding the optical and/or working properties he may have tried to achieve.